The Architecture of Qur’anic Disputation: A Tripartite Structural Model of Dialectics - Purwanto Purwanto; Muhammad Afifudin Dimyathi; Habib Abdillah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Although the Qur’an contains numerous dialogical passages that present debates between prophets and their opponents, the underlying structure of these arguments has rarely been examined through a systematic analytical framework. Existing studies on Qur’anic disputation tend to emphasize rhetorical or literary dimensions, while the logical and structural organization of Qur’anic dialectics remains relatively underexplored. This study investigates the argumentative structure of Qur’anic dialectics through a case analysis of the debate between Abraham and a king—commonly associated with Nimrod—in Surah al-Baqarah verse 258. Methodologically, the study combines philological analysis of Qur’anic dialectical terminology with an exegetical examination of classical tafsīr literature, particularly the works of al-Zarkashī, al-Suyūṭī, al-Zamakhsharī, and al-Rāzī. The analysis focuses on identifying the structural sequence of arguments and the conceptual foundations of Qur’anic dialectics as reflected in the exegetical tradition. The findings demonstrate that Qur’anic dialectics operates through a structured argumentative sequence consisting of three principal stages: the introduction of the claim, the elaboration of rational demonstration (ḥujjah), and the concluding refutation that exposes the logical weakness of the opponent’s argument. Philologically, the Qur’anic discourse of debate is articulated through several key lexical roots—j-d-l, ḥ-w-r, and ḥ-j-j—each of which reflects distinct dimensions of argumentative engagement. Furthermore, classical exegetical works reveal that Qur’anic disputation significantly influenced the later development of Islamic dialectical traditions, particularly in the literature of munāẓarah and theological debate. By integrating textual analysis with insights from the classical exegetical tradition, this study proposes a structural model of Qur’anic dialectics that highlights the interaction between rational demonstration, dialogical engagement, and rhetorical persuasion within Qur’anic discourse. The study thus contributes to a more systematic understanding of argumentative patterns in the Qur’an and their significance for the broader history of Islamic intellectual traditions.